PERAN PENDAMPINGAN BK TERHADAP KEPERCAYAAN SISWA DALAM BERKOMUNIKASI DIKELAS DENGAN MENGGUNAKAN BAHASA INDONESIA DI SMP SWASTA UTAMA MEDAN - Grumualdo Philippus Sipahutar; Jese Karona Imanuel Saragih; Kristian Nehemia Sianipar; Nur Aisyah Hidayat; Roy Sihombing; Sesilia Fransiska Br Ginting (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe and analyze the role of Guidance and Counseling (BK) services in increasing students' confidence in communicating in Indonesian in the classroom environment of Utama Medan Private Junior High School. The research background is based on the phenomenon of low active student participation in formal communication due to the dominance of regional languages, as well as the emergence of psychological barriers in the form of communication apprehension and defensiveness as a defense mechanism. This study used a descriptive qualitative approach with data collection techniques including observation, semi-structured interviews, and documentation. The research subjects included the guidance and counseling teacher, the Indonesian language teacher, and 20 seventh-grade students. The results indicate that low self-confidence is not solely a matter of limited vocabulary, but also a result of fear of failure and socialu stigmatization. Through a humanistic approach, guidance and counseling services have proven effective in changing students' perceptions, reducing emotional resistance, and building communication courage. Furthermore, cross-functional collaboration between guidance and counseling teachers and subject teachers, as well as the implementation of an inclusive literacy program, are key to successfully creating a learning environment that supports the development of students' communication skills.